The relationship of knowledge, power and freedom in The Damned Yard of Ivo Andrić - Soleša, Biljana S (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2019)
The paper deals with the relation of power, knowledge and freedom in the Damned Yard by Ivo Andrić. In this sense, the multiple meanings of the dungeon have been especially observed and analyzed; its routine and possible broader meanings are stated; the elements that open the approach to work as a universal allegory, with special reference to the characters of Karađoz, police officer, Ćamil and Džem-Sultan. Starting from M. Fuko’s attitudes, the central part, using the Karađoz’s game as an example, shows the mechanism and the exercising of power which is also revealed in the police officer’s actions during Ćamil’s arrest. The final part points to the recognition of the disciplinary concept of understanding and arranging the world in stories about Ćamil, Džem and Karađoz.